Przedsiębiorczość pozarolnicza w wybranych subregionach Karpat Polskich - Musiał, Wiesław (Entrepreneurship Outside Agriculture in Selected Subregions of the Polish Carpathians, 2006)
The paper analyses selected aspects of diversified off-farm economic activities of conducted dwellers in three peripherally situated subregions of the Polish Carpathians, i.e. the Beskid Żywiecki and Beskid Slaski Mountains (jointly), the Podhale Region and Tatra Mountains (the inhabited areas) and the Beskidy Mountains (including a part of the Sanocko-Turzanskie Mts.) also called The Lower Bieszczady Mts. The examined subregions reveal a great variability concerning the amount and intensity of economic subjects per 1 km2. Despite the fact that the Bieszczady subregion is even twice larger than the Beskidy region, the proportions concerning the number of operating economic entities are completely different. In the Bieszczady Mts. there are a total of only 2289 economic entities, whereas they are about 6.7 times more numerous in the Slaski and Żywiecki Beskid Mts.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 157-164